Exploring epigenetic resistance to infectious salmon anaemia in Atlantic salmon by genome-wide bisulfite sequencing in heart tissue - Ekvall, Hans (Norwegian University of Life Sciences, Ås, 2021)
The viral disease infectious salmon anaemia (ISA) is an ever-present threat to salmon farmers globally. Since its appearance it has been responsible for crises in the industry and has changed the way in which salmon are farmed. Disease resistance is an important phenotype that contributes to sustainable aquaculture production. The increasing understanding of epigenetics suggest a role for DNA methylation in the plasticity of an immune response and thereby an involvement in resistance to disease. Differences in methylation profiles between fish that are resistant or susceptible to the virus could reveal DNA methylation’s role in ISA resistance. Immune responses in Viral target tissues, particularly tissues affected early in disease progression, have the potential to slow and hinder disease before systemic effects take hold. In ISA this is well represented by heart tissue. To this aim, the most thorough method for whole-genome DNA methylation profiling was used to revealing 163 differentially methylated genes between survivors and early mortalities in an ISA cohabitation challenge test. Amongst these genes are genes involved in viral replication, antiviral innate immune response, and viral immune evasion that suggests a role played by epigenetics in resistance to ISA. submittedVersion EM-ABG